Buchbesprechung - Siltala Raimo (Duncker & Humblot, 2022)
A Treatise of Legal Philosophy and General Jurisprudence. Book Series. With Enrico Pattaro (Editor-in-Chief); Gerald J. Postema/Peter G. Stein (Associate Editors); Antonino Rotolo (Assistant Editor) and Individual Authors Responsible for Individual Volumes. Berlin u. a.: Springer 2007 - 2016.